Governance and Violence - Wallis, John (World Bank, Washington, DC, 2017)
This background paper addresses four questions. They may seem to be independent, but I hope to show they are closely connected. The questions are: 1) What did Weber say when he defined the modern state as the organization with a monopoly on the legitimate use of violence? 2) What conceptual framework might we bring to understand the dynamics of stability and growth in developing countries? Why do developing countries seem to be so susceptible to shocks and reversals? 3) What is the empirical evidence on economic shrinking (short run declines in annual per capita income), economic growing (short run increases in annual per capita income), and economic performance over the long run as measured by per capita income? 4) Is there a trade-off between security and growth, and how should we think about such a trade-off? All four points address in one way or another stability, instability, and social order. Weber may seem to be the least connected, but given the widespread use of his definition of the state and the focus on “a monopoly of violence” in the social science literature surrounding the political economy of development, it is the right place to start.